Highly Controllable Etchless Perovskite Microlasers Based on Bound States in the Continuum - Wang, Yuhan; Fan, Yubin; Zhang, Xudong; Tang, Haijun; Song, Qinghai; Han, Jiecai; Xiao, Shumin (ACS nano, 2021)
Lead halide perovskites have been promising materials for lasing applications. Despite that a series of perovskite microlasers have been reported, their lasing modes are confined by either the as-grown morphology or the etched boundary. The first one is quite random and incompatible with integration, whereas the latter one strongly spoils the laser performances. Herein, we propose and experimentally demonstrate a robust and generic mechanism to realize well-controlled perovskite microlasers without the etching process. By patterning a one-dimensional polymer grating onto a perovskite film, we show that the symmetry-protected bound states in the continuum (BICs) can be formed in it. The intriguing properties of BICs including a widely spread mode profile and high Q factor, associated with the exceptional gain of perovskite, produce single-mode microlasers with high repeatability, controllability, directionality, and a polarization vortex. This mechanism can also be extended to two-dimensional nanostructures, enabling BIC lasers with different topological charges.